A conceptual framework linking LM, TQM, QMS, and EMS practices with the SP: assessment of responses from managers of some Malaysian industries - Khalili, Amjad; Ismail, Md Yusof; Karim, A.N. Mustafizul; Daud, Mohd Radzi Che (Inderscience Publishers, 2018)
This paper presents a qualitative study for exploring the applicability of a proposed model consisting of a few important operations management (OM) practices by the verbatim responses gathered from some managers engaged in Malaysian industries. The OM practices which include lean manufacturing (LM), total quality management (TQM), environmental management system (EMS), and quality management system (QMS) are assessed for their relations to sustainable performance (SP). Studies conducted to assess such an integrated model involving the stated initiatives are rarely available especially from Malaysian perspective. A semi-structured interview protocol was developed and examined by academics to ensure its validity. Fifteen diverse managers from five manufacturing industries were interviewed. Findings from the thematic analysis indicate that managers in the manufacturing sector are adequately aware of these practices, understand the postulated benefits, and these practices are aligned with the OM theories